2015
DOI: 10.1177/1357633x15604555
|View full text |Cite
|
Sign up to set email alerts
|

Speech pathologists’ perspectives on transitioning to telepractice: What factors promote acceptance?

Abstract: Disclosure statement:Declaration of competing interests: Authors RR and CF are employed by an organization that delivers telepractice for speech pathology services and through whom all participants were recruited. Author JM is employed by an organization that works with clinicians, consumers and mangers to design and promote better health care, including via telehealth. Funding:The authors received no financial for the research, authorship, and/or publication of this article. Implementation of the telepractice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 10 publications
10
68
1
1
Order By: Relevance
“…The telehealth program should have sufficient mechanisms for delegation, collaboration, teamwork and feedback for maximising an effective TA and SLP partnership. This is consistent with the literature 31,40 .…”
supporting
confidence: 83%
“…The telehealth program should have sufficient mechanisms for delegation, collaboration, teamwork and feedback for maximising an effective TA and SLP partnership. This is consistent with the literature 31,40 .…”
supporting
confidence: 83%
“…This is consistent with other studies that have found that exposure to telepractice is associated with more positive beliefs regarding its use (175,176,182,183,219). Tucker (175) has suggested that SLPs with greater awareness, experience, and confidence in the use of telepractice will be more willing to implement it with their patients.…”
Section: Speech-language Pathologists' Experiences Of Providing Telepsupporting
confidence: 89%
“…• negative perceptions (175,176,180) • reduced understanding (176,180) • a lack of training (179,180,183) • a need for assessment and therapy tools that have been adapted for the telepractice environment (175,182,183) • a desire for more professional standards, research evidence, and guidelines (175,176,178,180,182) • concerns about equipment and technology (175,(178)(179)(180)(181)(182)(183) • a lack of information and communications technology (ICT) support (182) • concerns about time required for consults, and to establish a telepractice service (176,179) • a lack of funding and difficulty with reimbursement (175,176,(178)(179)(180)182) • concerns about patient confidentiality (176)…”
Section: Efficacy and Adoption Of Speech Pathology Telepracticementioning
confidence: 99%
See 2 more Smart Citations